Does Social Media Usage Reduce the Level of Religiosity? - Chusjairi, Juni Alfiah; Sudarmanti, Rini (Universitas Semarang, 2024)
Introduction: This study examined the interplay between social media usage and religiosity among Indonesian Muslims, which is the largest Muslim country in the world. Morevoer where more than 70% of the population are active on social media. The social media platforms included in the study were networking sites such as facebook, to microblogging platforms such as Twitter and Instagram. Video sharing services such as YouTube were also examined. Methods: Data were collected through an online survey, and Structural Equation Modelling with AMOS was employed for analysis. The respondents were millennial graduate students studying communication. Structural Equation Modeling was chosen due to its suitability for multivariate analysis involving latent variables, which are not directly measurable, such as religiosity and social media usage. The dimension used to analyse the relationship with God which includes assessing ones’ religiosity and the second dimension includes, non-obligatory actions which is more to religious acts. Findings: Results of the study indicated a negative association between social media usage and religious devotion, with greater social media engagement correlating to reduced time devoted to religious practices and spiritual connection with Allah. In other words it showed that the more active someone used social media, the lower the religiosity. Originality: This research provided new insights into how digital technologies influenced religious practice in modern era. It affects how people practice, engage with, communicate through social media for spiritual expression, and community building outreach. It also brings concern in ethical reflection, intelligent engagement, and discernment within religious communities.